CONCEPT OF APPRAISAL INSTITUTIONS IN ASSESSING THE VALUATION OF INTANGIBLE ASSETS ON SMALL MEDIUM ENTERPRISES INTELLECTUAL PROPERTY AS OBJECT OF CREDIT GUARANTEE TO IMPROVE COMMUNITY'S CREATIVE ECONOMY - Anis Mashdurohatun; Gunarto Gunarto; Oktavianto Setyo Nugroho (UNISSULA, 2021)
This study aims to analyze the factors that affect the effectiveness of Intangible Assets of Intellectual Property of Small and Medium Enterprises as objects of credit guarantees, and the concept of appraisal institutions in assessing the valuation of intangible assets of intellectual property of Small and Medium Enterprises as objects of credit guarantees in order to improve the creative economy of the community. The method used in this research is empirical juridical. The data used are primary data and secondary data. Data collection techniques data collection through library research and field studies (through questionnaires, focus group discussions, and interviews). The results of the study found that the five factors that affect the effectiveness of Intangible Assets intellectual property of Small and Medium Enterprises as objects of credit guarantees are legal factors, law enforcement, infrastructure, society and culture. The legal factor that affects is there is no special legal product for public appraisers of IPR Intangible assets. In the practice, IPR intangible assets have not been accepted by all banks as objects of basic guarantees but only as objects of additional guarantees. It is caused by no trust from the bank toward the value of IPR as basic guarantees, there have been no appraisal institutions, and there is not intellectual property rights market yet, that makes IPR is not commonly used by banks and SMEs as IP owners. The concept of appraisal institutions in assessing the valuation of intangible assets of intellectual property of small and medium businesses as objects of credit guarantees, in order to improve the creative economy of the community, is necessary to form an appraisal agency through the products of laws and regulations. These regulations, among others, regulate the intangible assets of IPR, the purposes and objectives of the IPR assessment, the requirements to become an IPR appraiser, the function and authority of IPR assessment, the valuation method used, and so on.